'Rudely Interrupted': Shakespeare and Terrorism. - Holderness, Graham; Loughrey, Bryan (Critical Survey, 2007)
The article discusses a terrorist attack at a theater in Qatar presenting the theatrical production "Twelfth Night," by William Shakespeare. Omar Ahmed Abdullah Ali, an employee of Qatar Petroleum, drove a car bomb into the theater, killing the play's director Jonathan Adams. The alleged terrorist group Jund Al-Sham took credit for the bombing. The author suggests the theater company represented a target symbolizing Western and Christian culture.